Arsenic removal from water by starch functionalized maghemite nano-adsorbents: Thermodynamics and kinetics investigations - Siddiqui, Sharf Ilahi; Singh, Prakash Narayan; Tara, Nusrat; Pal, Shaili; Chaudhry, Saif Ali; Sinha, Indrajit (Colloid and interface science communications, 2020)
Arsenic is a highly toxic element present in water which needs to be removed from the water to eliminate its adverse health effects on human beings. But the concentration in most natural sources of water is deficient. Therefore investigations for its elimination from dilute aqueous solutions were carried out for obtaining potable water. Fabrication of As(III) specific magnetically recyclable stable nano-adsorbents would be an effective way of solving this tricky problem. The present study investigated the As(III) removal from low concentration aqueous solutions by magnetically recyclable superparamagnetic starch functionalized maghemite nano-adsorbents. For the sake of comparison, arsenic removal from its dilute aqueous solution was carried using both starch functionalized and non-functionalized maghemite nanoparticles as adsorbents. Functionalization by starch led to a significant increase in the As(III) adsorption capacity of the maghemite. The data obtained for arsenite adsorption was found to fit the Freundlich isotherm model, while the kinetics of the adsorption followed the pseudo-second-order model. The maximum Langmuir adsorption capacities achieved for virgin maghemite and functionalized maghemite were 7.14, 7.46, and 7.35 mg/g, and 8.57, 8.88, and 8.67 mg/g at 27, 35 and 45 °C, respectively. The negative value of ∆G (−7.13, −7.21, and −7.50 kJ/mol, for γ-Fe2O3; and −5.50, −5.45 and −5.98 kJ/mol for γ-Fe2O3@starch, at 27, 35 and 45 °C, respectively) indicated the feasibility and spontaneity of the As(III) adsorption on both adsorbents. The negative values of ∆H (−0.0016 kJ/mol for γ-Fe2O3; and −0.00022 kJ/mol for γ-Fe2O3@starch) showed that the adsorption process was exothermic. [Display omitted] •The starch functionalized maghemite nanoparticles is being reported first time.•The functionalized maghemite nanoparticles were used for the removal of arsenic.•Functionalized maghemite nanoparticles exhibited good adsorption activity for As(III).•The adsorption followed Freundlich isotherm thus the surface of nanoparticles exhibited hetrogeneity.•The kinetic data followed pseudo-second order and film diffusion model.